1994
DOI: 10.1021/cm00039a009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Polymerization of Multiple Aromatic Ether Phthalonitriles

Abstract: Multiple aromatic ether-linked phthalonitrile polymers have been synthesized and characterized. The oligomeric monomers are prepared from reaction of an excess amount of a bisphenol such as 4,4'-(hexafluoroisopropy1idene)bisphenol or 4,4'-dihydroxybiphenyl with 4,4'-difluorobenzophenone in the presence of either weak or strong bases in N-methylpyrrolidinone (NMP) as solvent, followed by end-capping with 4-nitrophthalonitrile. The oligomeric phthalonitrile monomers were cured in the presence of a minute quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 0 publications
4
126
0
Order By: Relevance
“…These results revealed that the sample of the 3-APN monomer heated during the experiments exhibited relatively high glass transition temperatures and thermal polymerization reaction of the nitrile groups progressed at an extremely slow rate [23]. This is related to the fact that the nitrile curing reaction in the phthalonitrile-amine compositions was controlled as a [15,21,28].…”
Section: Self-promoted Curing Properties Of 3-apn Monomer and Prepolymermentioning
confidence: 95%
See 2 more Smart Citations
“…These results revealed that the sample of the 3-APN monomer heated during the experiments exhibited relatively high glass transition temperatures and thermal polymerization reaction of the nitrile groups progressed at an extremely slow rate [23]. This is related to the fact that the nitrile curing reaction in the phthalonitrile-amine compositions was controlled as a [15,21,28].…”
Section: Self-promoted Curing Properties Of 3-apn Monomer and Prepolymermentioning
confidence: 95%
“…The exothermic transition peaked at 239°C and the enthalpy of cure was 179.3 J/g, which were a result of self-promoted curing reaction of the 3-APN monomer between the amino group and phthalonitrile units. For these phthalonitrile monomers [9][10][11][12][13][14][15][16][17][18][19][20][21], the polymerization reaction occurs through the nitrile groups of the phthalonitrile units in the presence of aromatic diamine curing agents and these exothermic transitions of the cure reaction peaked at 250-270°C. In addition, the maximum processing temperature was up to 425°C and the heat-treatment time was very long (> 10 h) due to the low reactivity of the phthalonitriles.…”
Section: Self-promoted Curing Properties Of 3-apn Monomer and Prepolymermentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitation procedure was carried out several times. The polymer was further purified by Soxhlet extraction from acetone for 24 h and then dried under vacuum at 150°C for 24 h. Characterization 1 H NMR (400 MHz) and 13 C NMR (100 MHz) spectra were measured on a Bruker Avance-400 NMR spectrometer with DMSO-d 6 as the solvent and tetramethylsilane as the internal standard. IR spectra were recorded with a Nicolet FTIR-460 Fourier transform infrared spectrometer by KBr pellet.…”
Section: Polymer Synthesismentioning
confidence: 99%
“…On the other hand, oligomer or monomer with phthalonitrile end group have been confirmed to be able to undergo thermal polymerization through the nitrile groups on phthalonitrile units by an addition mechanism to afford heterocyclic crosslinked products, such as triazine, phthalocyanine, and isoindoline [12][13][14][15][16][17]. Aromatic diamine, phenol, and strong organic acid were frequently used as the curing agents [18].…”
Section: Introductionmentioning
confidence: 99%